Phenotypic Switch of Human Peritoneal Macrophages during Childhood - Schukfeh, Nagoud; Elyas, Amr; Viemann, Dorothee; Ure, Benno M.; Froemmel, Stephanie; Park, Joon-Keun; Kuebler, Joachim F.; Vieten, Gertrud (European Journal of Pediatric Surgery, 2021)
Introduction Human peritoneal macrophages are resident in the abdominal cavity where they support the specific microenvironmental regulation. We have previously observed a phenotypic switch of murine macrophages during infancy that was associated with a functional development. To investigate the age related changes in human peritoneal macrophages, we analyzed peritoneal macrophages of children undergoing laparoscopic procedures. Materials and Methods Immunologically healthy children who received minimally invasive surgery in our department were included in this study. In all cases, the written consent was obtained. At the beginning of laparoscopy, physiologic NaCl-solution was instilled and manually removed through the umbilical trocar to gain macrophages. Lavage cells were processed for flow cytometry analysis. CD14+ myeloid cells were monitored for specific lineage marker expression. Results A total of 21 donors (age: 7 days-18 years) were included and divided into three groups. In all age groups, 97% of myeloid cells expressed CD11b. 70% of these expressed CD14. Three subsets of CD14 cells were detected on the basis of CD14/CD16 expression (CD14 + CD16dim, CD14 + CD16inter, and CD14 + CD16high). In neonates, >80% belonged to the CD14 + CD16high subset, reducing to 30% in adolescents. In none of the cases, the M2 markers CD23 and CD25 were expressed. Conclusion This is the first study showing that lineage marker expression of peritoneal macrophages in neonates differs from that in adults. The knowledge about neonatal tissue resident macrophages might help to understand their complex interaction and to use specific macrophage properties for therapeutic approaches.
CRIS-Team Scopus Importer:2023-03-23
Keywords: cell population; laparoscopy; leukocytes; neonatal; pediatric surgery